论新加坡与香港小说里的文化碰撞 ：以黄孟文《毛果山传奇系列》及也斯《剪纸》为例 = Culture clashes in stories of Singapore and Hong Kong : a case study of the legend of Mau-Fruit Mountain & Paper Cut-outs - 李依徽 Lee, Yee Wei (2011)
新加坡和香港两地同样有过一段相近的殖民地历史，受过西方文化的“入侵”，并一直受现代美国为主的西方文化等影响，与本源中国文化产生一定程度的碰撞、摩擦及交融。但两地情况不同，又致使中西文化的后续发展出现差异，而这些特殊的文化现象往往能在香港及新加坡的文学作品中呈现。本论文以新加坡作家黄孟文的微型小说《毛果山传奇系列》及也斯的小说《剪纸》为例，分别从两部文学作品所呈现的中西文化碰撞，去体现并探讨新加坡和香港各自相同及不同的社会状况和历史发展，之后再比较两部小说中表现的新港中西文化发展，对两地中西文化发展的异同进行比较，再对两地同中有异的特殊文化现象进行总结。Singapore and Hong Kong owned the similar colonial history which caused the “invasion” of Western culture with the constant influences from modern America. As a result, clashes, conflicts and fusion occurred between the Chinese and Western culture. However, the distinctive political issues have led both cultures into different follow-up development and these phenomenons tend to be shown in stories of Singapore as well as Hong Kong. The Legend of Mau-Fruit Mountain by Huang MengWen and Paper Cut-outs by Ye Si will be the case study of my thesis and the social condition and history development shown in both stories will be the main investigation. Besides, cultural development in Singapore and Hong Kong will be compared by side through these stories and, thus, comes to the conclusion of the cultural deviance in these cities.